ANALISIS FAKTOR PENYEBAB PERNIKAHAN USIA MUDA - Pauziah, Pauziah; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis isâ€Analysis of the Causes of Marriage for Young Age the problem in this study is how the Factor Analysis Causes the marriage of a young age, which is seen in terms of (1) education, (2) economy, and (3) motivation of parents. This study aims to determine the factors that cause young marriage In this study the method used is qualitative with descriptive analysis,In this study the method used is qualitative with descriptive analysis,The results of the study (1) the factors that cause young marriage to occur are caused by low levels of education of children and parents so that parents who do not have the costs and are unable to provide adequate needs to continue their education, so children prefer to marry to reduce the burden on the family, (2) the factors that cause young marriages to occur because of the economy, a low economy is also a barrier for children to continue their education and prefer to work and get married at a young age, a small amount of parental work and income that cannot meet their daily needs (3) the factors that cause young marriage to occur because of motivation, as any parent has been done to make children better, by giving input, advice, motivation and enthusiasm but most children abuse what parents have given one of them is not listening advice and advice from parents not to marry at a young age.Keywords: Cause Factors, Parents, Young Age Marriage, Bunut.